Navigating Trends of Marketing Innovations in the Hospitality and Tourism Industry: A Comprehensive Review - Husni Muhamad Rifqi (Yayasan Ghalih Pelopor Pendidikan, 2025)
The hospitality and tourism industry is undergoing rapid transformation driven by technological advancements, evolving consumer behaviours, and external disruptions. This study investigates marketing innovations within the sector, with a particular emphasis on digital transformation, AI-driven personalisation, big data analytics, and emerging technologies such as blockchain and virtual reality. It further examines the impact of global crises, notably the COVID-19 pandemic, on marketing strategies, highlighting shifts in consumer engagement and business resilience. Employing a qualitative literature review, the study synthesises insights from peer-reviewed journals and conference proceedings sourced from Scopus, Web of Science, Google Scholar, and ScienceDirect. Through a narrative synthesis approach, key trends, challenges, and gaps in hospitality marketing research are identified. The findings suggest that although digitalisation and AI contribute to enhanced consumer engagement and improved business performance, significant challenges remain, including concerns around data privacy, resource limitations, and barriers to adoption. This study offers practical implications for businesses seeking to optimise marketing strategies and outlines avenues for future research. Notable limitations include a reliance on secondary data and the need for empirical validation of emerging trends.